Influence of risk perception and policy support on the deviation of rural households’ demands and adoption behavior of the forestry socialized service - Liao, Wenmei; Yuan, Ruolan; Zhang, Xu; Zhang, Chang; Li, Na (Frontiers in Environmental Science, 2023)
This study explores the impact mechanism of risk perception and policy support on the deviation of rural households’ demands and adoption behavior (RHDAB) of the forestry socialized service (FSS). It provides a decision-making basis for promoting the construction of a collective FSS system and realizing the value of ecological products. Survey data from 787 rural households in Zhejiang, Fujian, and Jiangxi provinces were used to quantify the influence of risk perception and policy support on the deviation of RHDAB of the FSS using the Mv-probit model and Poisson model. The results revealed that: (1) there were deviations between RHDAB for different types of FSS, with 57.71% and 66.20% for good seeds and cultivation technology services and product collection and marketing services, respectively. (2) Risk perception accelerated the deviation and degree of deviation between RHDAB of the FSS, particularly the technology risk perception. Meanwhile, policy support was shown to mitigate the effect of risk perception on rural households' deviation and deviation degree. (3) Business risk perceptions had a more significant impact on the deviation of RHDAB in middle and high-economic development areas compared to technology risk perception and financial risk perceptions in low-economic development areas. Additionally, business risk perception was found to have a significant positive effect on the deviation of small and large operation-scale rural households, while technology risk perception significantly impacted the deviation of small operation-scale rural households. Consequently, this study suggests the need for a sound forestry risk management system to address the variability of the deviation of RHDAB across different regions and operation scales, as well as to improve the service quality of forestry insurance, accelerate the speed and benefit of inclusive rural finance, and cultivate new supply bodies of socialized services, thereby promoting the construction of collective FSS system and realizing the value of ecological products.